Recombinant factor XIII prophylaxis is safe and effective in young children with congenital factor XIII‐A deficiency: international phase 3b trial results. (10th July 2017) - Kerlin, B. A.; Inbal, A.; Will, A.; Williams, M.; Garly, M.‐L.; Jacobsen, L.; Kearney, S. L.
Abstract : Essentials Prophylaxis is the standard of care for congenital factor XIII‐A (FXIII‐A) deficiency. Six children with FXIII‐A deficiency received once‐monthly prophylaxis with recombinant FXIII‐A. Prophylaxis was well tolerated and no anti‐FXIII antibodies were detected. Prophylaxis was effective with an annualized bleeding rate of zero. Summary: Background: Factor XIII deficiency is a rare, severe congenital bleeding disorder. Monthly prophylaxis with recombinant FXIII A‐Subunit (rFXIII) has demonstrated favorable safety and efficacy in patients aged ≥ 6 years, and may similarly benefit younger children. Objective: To evaluate the long‐term safety and efficacy of rFXIII in children aged < 6 years with congenital FXIII A‐subunit deficiency. Patients/methods: Six children, who had previously completed a single‐dose pharmacokinetic trial of rFXIII, received 35 IU kg −1 rFXIII every 28 days (± 2 days) for a minimum of 52 weeks, and were evaluated for bleeding and adverse events. The Berichrom FXIII activity assay was used to monitor FXIII activity. Results: The children, three girls and three boys, had an average age of 3.0 years (range: 1–4 years) at enrollment. The total treatment duration was 1.8–3.5 years, giving a total of 16.6 patient‐years. No antibody development, thromboembolic events or allergic reactions occurred. There were 93 mild and seven moderate adverse events. Two adverse events (lymphopenia and gastroenteritis) were reported as probably or possibly related to rFXIII in two children. Two serious adverse events, unrelated to rFXIII, were reported in a single child, each related to head injury, and neither resulting in intracranial hemorrhage. The geometric mean FXIII activity trough was 0.19 IU mL −1 . No bleeding episodes requiring treatment with an FXIII‐containing hemostatic agent occurred during the trial; thus, the annualized bleeding rate was 0. Conclusions: Consistent with data from older age groups, prophylaxis with rFXIII appears to be safe and effective in young children with congenital FXIII A‐subunit deficiency.